2011
DOI: 10.1111/j.1708-8208.2011.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Displacement of Dental Implants in Trabecular Bone under a Static Lateral Load in Fresh Bovine Bone

Abstract: Displacement of screw implants in trabecular bone can be detected and visualized using commercially available endoscopes with a high magnification. A lateral load of 20 N indicates a mean displacement of over 100 µm and therefore results in a critical displacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…8,9 Implant micromovements exceeding 150 mm may have detrimental effects on implant osseointegration and may increase the risk of early failure. [12][13][14][15] A second surgery is needed to uncover the implant and connect the implant abutment. Nonsubmerged healing is less invasive and shortens the time of implant loading and prosthesis delivery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Implant micromovements exceeding 150 mm may have detrimental effects on implant osseointegration and may increase the risk of early failure. [12][13][14][15] A second surgery is needed to uncover the implant and connect the implant abutment. Nonsubmerged healing is less invasive and shortens the time of implant loading and prosthesis delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Primary implant stability allows for bone formation that increases the bone-to-implant contact. 12 Engelke et al 15 have concluded that an insertion torque greater than 30 Ncm is advisable to achieve adequate primary stability and a torque value #11 Ncm is considered a risk factor that increases the likelihood of implant failure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two fresh bovine mandibles were prepared due to the similarity of their density and mineral content to human bone. 26,27 To prevent dehydration, they were covered in a wet towel at a temperature of 4ºC. Then, because of appropriate density, 10 holes with a diameter of 4 mm were embedded at 2-cm intervals from each other by a 4-mm drill in the angle and ramus of one mandible under cooling with normal saline using an irrigating syringe.…”
Section: Methodsmentioning
confidence: 99%